Mental Health in German Paralympic Athletes During the 1st Year of the COVID-19 Pandemic Compared to a General Population Sample - Aglaja Busch; Aglaja Busch; Aglaja Busch; Eva Johanna Kubosch; Antonia Bendau; Rainer Leonhart; Verena Meidl; Berit Bretthauer; Moritz Bruno Petzold; Petra Dallmann; Nina Wrobel; Jens Plag; et al. (Frontiers Media S.A., 2022)
IntroductionThe COVID-19 pandemic has huge influences on daily life and is not only associated with physical but also with major psychological impacts. Mental health problems and disorders are frequently present in elite paralympic athletes. Due to the pandemic situation, new stressors (e.g., loss of routine, financial insecurity) might act upon the athletes. Therefore, the assessment of mental health in athletes during the COVID-19 pandemic is important to identify prevalence of psychological problems and propose countermeasures.MethodsThe mental health of German paralympic athletes was longitudinally monitored (starting in May 2019). The athletes completed the Patient Health Questionnaire 4 (PHQ-4) on a weekly basis and reported a stress level, training hours, and training load. During the pandemic, 8 measurement time points (March 2020 to April 2021) were used to reflect the psychological health course of the athletes. In parallel, a convenience sample of the general population was questioned about their psychological distress, including the PHQ-4. To be included in the analysis, participants of both groups had to complete at least 4 measurement time points. Matching of the para-athletes and the general population sample was prioritized upon completion of the same measurement time points, gender, and age.ResultsSeventy-eight paralympic athletes (40 women, 38 men, age: 29.8 ± 11.4 years) met the inclusion criteria. Seventy-eight matched pairs of the general population (40 women; 38 men; age: 30.5 ± 10.9 years) were identified. The para-athletes had a significantly (p <0.0001; 0.39 < r <0.48) lower PHQ-4 value at each measurement time point compared to the matched control group. No significant age or sex differences were evident regarding the symptom burden. In para-athletes, no significant and a weak positive correlation was found between decreased training load and PHQ-4 values and a stress level, respectively. Reduced physical activity was significantly (p <0.0001) associated with higher PHQ-4 values in the general population sample.DiscussionLower PHQ-4 values were reported by the para-athletes compared to the general population sample. However, small sample sizes must be considered while interpreting the data. Nevertheless, adequate support for individuals suffering from severe psychopathological symptoms should be provided for para-athletes as well as for the general population.